Morality of China in Africa : the Middle Kingdom and the Dark Continent - Chan, Stephen, 1949- (London : New York : Zed Books, 2013)
"Edited with authority by the influential and respected Stephen Chan, this unique collection of essays gathers together for the first time both African and Chinese perspectives on China's place in Africa. The book starts with an excellent introductory essay from Stephen Chan, written in his usual elegant prose and featuring some very fresh insights organised with great clarity. Featuring useful historical context, this brave book analyses the 'moral' aspects of the policies and ensuing migration. The book completely undermines existing assumptions concerning Sino-African relations, such as that Africa is of critical importance for China; that China sees no risk in its largesse towards Africa; and that there is a single Chinese profile/agenda. The resulting collection touches the issue of racism but is equally about moments of pure idealism and 'romance' in Sino-African history."--Publisher's website.
Part 1: The Middle Kingdom and Dark Continent: An essay on China, Africa, and many fault-lines / Stephen Chan. -- Part 2: Chinese responses. Sino-African cultural relations: Soft power, cultural statecraft and international cultural governance / Jerry C.Y. Liu ; From revolution to business: China's changing discourses on Africa / Qing Cao ; Zhuge Liang and Meng Huo: A metaphor for Sino-African relations? / L.H.M. Ling ; Back to basics: It could be anyone and, anyway, it's all hard work / Xiaoming Huang. -- Part 3: African outlooks. China and Africa: An African view / Patrick Mazimhaka ; Competition or partnership? China, United States and Africa -- An African view The African members of the Trilateral Dialogue on China, Africa and the United States / Lopo do Nascimento, William Lyakurwa, Patrick Mazimhaka, Greg Mills, Joe Molo, Sydney Mufamadi, Michael Spicer -- And what about India and Africa? The road ahead / Sumit Roy -- The future of China and Africa / Stephen Chan.
Includes bibliographical references and index.
Keywords: 2; 2; Politische Ethik; International relations; China -- Relations -- Africa; Africa -- Relations -- China; China -- Foreign relations -- Moral and ethical aspects; China; Afrika; Africa; China